Pengaruh Komitmen Organisasi dan Kompetensi Guru Terhadap Kinerja Guru Dimoderasi Oleh Budaya Sekolah (Studi Pada Guru PNS Sekolah Dasar diKorwil Bidang Pendidikan Kecamatan Subah Kabupaten Batang) - yuli yuliati; Lie Liana (Faculty of training and education, Pamulang university, 2022)
ABSTRACTThis study aims to determine how the influence of organizational commitment and teacher competence on teacher performance is moderated by school culture on elementary school civil servants teachers in the Regional Coordinator for Education, Subah District, Batang Regency. The population in this study were all PNS Elementary School Teachers in Subah District, totaling 108 teachers. The results of this study indicate that organizational commitment has no effect on teacher performance. Teacher competence has a positive and significant influence on teacher performance. School culture has no influence on teacher performance. School culture moderates the relationship between organizational commitment to teacher performance. School culture weakens the influence of teacher competence on teacher performance. Keywords: Organizational commitment; Teacher competence; Teacher performance; School culture.